EVALUATION OF MATERIAL NONLINEARITY IN FATIGUED SAMPLES USING AN IMPROVED LAMB-WAVE NONLINEAR PARAMETER - A. Masurkar, Faeez (2021)
The present study focuses on estimating the material nonlinearity of thin fatigued plate specimens using an improved amplitude-based Lamb wave nonlinear parameter. This parameter depends on the spectral amplitudes of the fundamental and second harmonics of Lamb waves generated because of the material nonlinearity. The cumulative effect required for an effective propagation of second harmonic is achieved using the resonant 0 − 0 and 1 − 2 mode pair that works on approximate phase velocity matching at a low-frequency region and strict phase and group velocity matching at a high frequency region respectively. The material nonlinearity is also evaluated using a Physics based nonlinear parameter that depends on the second and third order nonlinear elastic constants and is independent of the propagation distance thereby giving the global material nonlinearity. It is found that for a pristine state, the peak of amplitude-based parameter equals the physics based one and for a fatigued state, the amplitude-based parameter keeps increasing with an increase in fatigue damage. In contrast, the conventional relative nonlinear parameter is found to be useful for qualitative estimation of material nonlinearity. Thus, for a quantitative estimation, the improved nonlinear parameter is found to be more useful.